In Search for Human Dignity: the Earthquakes of February 6, 2023, and Their Impact on Interreligious Relations in Antakya, Hatay - Kreinath, Jens (Mission studies, 2024)
This article aims at addressing the question of human dignity in the face of the suffering that people of the city of Antakya (formerly Antioch) experienced after the devastating earthquakes on February 6, 2023. The main question the article raises is concerned with the impact the destruction of shared sacred sites has on the heritage of the city and the dynamics of intercultural and interreligious relations among its different communities. The theoretical argument is that human dignity must be conceptualized in relational terms as a dynamic force that captures the human potential to shape relations among different communities.